An international validation study of the IL-2 Luc assay for evaluating the potential immunotoxic effects of chemicals on T cells and a proposal for reference data for immunotoxic chemicals. (August 2020) - Kimura, Yutaka; Yasuno, Rie; Watanabe, Mika; Kobayashi, Miwako; Iwaki, Tomoko; Fujimura, Chizu; Ohmiya, Yoshihiro; Yamakage, Kohji; Nakajima, Yoshihiro; Kobayashi, Mayumi; Mashimo, Nana; Takagi, Yumi; et al.
Summary: To evaluate the immunotoxic effects of xenobiotics, we have established the Multi-ImmunoTox assay, in which three stable reporter cell lines are used to evaluate the effects of chemicals on the IL-2, IFN-γ, IL-1β and IL-8 promoters. Here, we report the official validation study of the IL-2 luciferase assay (IL-2 Luc assay). In the Phase I study that evaluated five coded chemicals in three sets of experiments, the average within-laboratory reproducibility was 86.7%. In the Phase II study, 20 coded chemicals were evaluated at multiple laboratories. In the combined results of the Phase I and II studies, the between-laboratory reproducibility was 80.0%. These results suggested that the IL-2 Luc assay was reproducible both between and within laboratories. To determine the predictivity, we collected immunotoxicological information and constructed the reference data by classifying the chemical into immunotoxic compounds targeting T cells or others according to previously reported criteria. When compared with the reference data, the average predictivity of the Phase I and II studies was 75.0%, while that of additional 60 chemicals examined by the lead laboratory was 82.5%. Although the IL-2 Luc assay alone is not sufficient to predict immunotoxicity, it will be a useful tool when combined with other immune tests. Highlights: IL-2 luciferase assay can evaluate the effects of xenobiotics on the activation of IL-2 promoter. The IL-2 luciferase assay was reproducible both between and within laboratories in the validation. The reference data to classify immunotoxic compounds was constructed referring to published data. Compared with the reference data, the predictivity was 75.0% in the validation study.